2010
DOI: 10.1007/s00792-010-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity of soil in the vicinity of Pindari glacier, Himalayan mountain ranges, India, using culturable bacteria and soil 16S rRNA gene clones

Abstract: Three 16S rRNA gene clone libraries (P1L, P4L and P8L) were constructed using three soil samples (P1S, P4S and P8S) collected near Pindari glacier, Himalayas. The three libraries yielded a total of 703 clones. Actinobacteria, Firmicutes and Proteobacteria were common to the three libraries. In addition to the above P1L and P8L shared the phyla Acidobacteria, Bacteroidetes, Gemmatimonadetes and Planctomycetes. Phyla Chlamydiae, Chlorobi, Chloroflexi, Dictyoglomi, Fibrobacteres, Nitrospirae, Verrucomicrobia, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 58 publications
9
28
1
Order By: Relevance
“…Cyanobacteria are the predominant biota in cold polar environments and play an important role in the carbon and nitrogen economy of tundra and polar desert soils (Bonilla et al 2005;Adams et al 2006;Vincent 2007;Varin et al 2012). This photosynthetic phylum is either reported to be present in low frequency or absent in the Himalayan regions (Pradhan et al 2010;Shivaji et al 2011;Stres et al 2014). Gemmatimonadetes and Verrucomicrobia found in the present study were reported from other cold habitats, though at a low frequency (Steven et al 2007;Wagner et al 2009;Pradhan et al 2010;Wu et al 2012).…”
Section: Discussionsupporting
confidence: 53%
“…Cyanobacteria are the predominant biota in cold polar environments and play an important role in the carbon and nitrogen economy of tundra and polar desert soils (Bonilla et al 2005;Adams et al 2006;Vincent 2007;Varin et al 2012). This photosynthetic phylum is either reported to be present in low frequency or absent in the Himalayan regions (Pradhan et al 2010;Shivaji et al 2011;Stres et al 2014). Gemmatimonadetes and Verrucomicrobia found in the present study were reported from other cold habitats, though at a low frequency (Steven et al 2007;Wagner et al 2009;Pradhan et al 2010;Wu et al 2012).…”
Section: Discussionsupporting
confidence: 53%
“…Verrucomicrobia, Chloroflexi, Gemmatiomonadetes, Bacteroidetes, Planctomycetes, Nitrospira, Deinococcus-Thermus and Armatimonadetes were present in one or two libraries but the frequency of distribution was truncated. These observations are in accord with some other earlier studies [51]- [53].…”
Section: Phylogenetic Structure Of Microbial Communitiessupporting
confidence: 94%
“…At five glacier forefields near Ny-Ålesund, Svalbard, the mean total cell count was 6.5 x 10 7 cells g -1 (Kaštovská et al, 2005), and at Pindari Glacier in the Himalayas it ranged between 2.2 and 8.7 x 10 8 cells g -1 sediment (Shivaji et al, 2011). Based on these studies, the magnitude range of proglacial communities is within 10 7 -10 9 cells g -1 sediment.…”
Section: Microbial Community Structuresmentioning
confidence: 73%